2020
DOI: 10.5606/tgkdc.dergisi.2020.18685
|View full text |Cite
|
Sign up to set email alerts
|

Does uncontrolled diabetes mellitus affect cerebral hemodynamics in heart surgery?

Abstract: Bu çalışmada, koroner arter baypas greftleme yapılan hastalarda çeşitli nöromonitörler ile kötü kan glukoz kontrolünün ameliyat sırası serebral sistem üzerine etkisi araştırıldı. Ça lış m a pla nı: Ocak 2011-Aralık 2011 tarihleri arasında elektif koroner arter baypas greftleme planlanan toplam 40 erişkin hasta (31 erkek, 9 kadın; ort. yaş 58.8±9.2 yıl; dağılım, 38-78 yıl) çalışmaya alındı. Hastalar hemoglobin A1c düzeylerine göre şu şekilde dört gruba ayrıldı: Grup 1, diyabetik olmayan kontroller (n=11); Grup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…We found that patients with a history of diabetes or previous cerebral infarction were more likely to develop impaired CA after CPB with MHCA (Table 1). This was consistent with previous work suggesting that diabetes may associate with the occurrence of impaired CA by inducing cerebral microvascular endothelial dysfunction and cardiovascular autonomic neuropathy [31][32][33] . The previous cerebral infarction may weaken or damage the response of CBV to changes in blood pressure [34,35] .…”
Section: Discussionsupporting
confidence: 93%
“…We found that patients with a history of diabetes or previous cerebral infarction were more likely to develop impaired CA after CPB with MHCA (Table 1). This was consistent with previous work suggesting that diabetes may associate with the occurrence of impaired CA by inducing cerebral microvascular endothelial dysfunction and cardiovascular autonomic neuropathy [31][32][33] . The previous cerebral infarction may weaken or damage the response of CBV to changes in blood pressure [34,35] .…”
Section: Discussionsupporting
confidence: 93%
“…Preoperative evaluation is the important part to determine the high risk patients such as diabetics and further examinations like transcranial doppler may be helpful. Transcranial Doppler is a non-invasive ultrasound which provides neuromonitoring and evaluation of the middle cerebral artery flow velocity, which carries 75 to 80% of the carotid artery blood flow that responsible of the cerebral blood flow (13).…”
Section: Discussionmentioning
confidence: 99%
“…Neurological and neurocognitive impairments are among the most serious of these complications. [ 1 - 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Three main mechanisms are held responsible for POND: microembolism, insufficient cerebral perfusion, and systemic inflammatory response. [ 3 , 5 ] The CABG patients are often accompanied by advanced age, carotid artery stenosis, and diabetes mellitus (DM), which may all increase the risk of POND. The incidence of POND in the early postoperative period after CABG varies between 20 and 50%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation